2015
DOI: 10.1038/ncomms7941
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Bacillus subtilis 70S ribosome reveals the basis for species-specific stalling

Abstract: Ribosomal stalling is used to regulate gene expression and can occur in a species-specific manner. Stalling during translation of the MifM leader peptide regulates expression of the downstream membrane protein biogenesis factor YidC2 (YqjG) in Bacillus subtilis, but not in Escherichia coli. In the absence of structures of Gram-positive bacterial ribosomes, a molecular basis for species-specific stalling has remained unclear. Here we present the structure of a Gram-positive B. subtilis MifM-stalled 70S ribosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
163
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(178 citation statements)
references
References 61 publications
15
163
0
Order By: Relevance
“…The in vitro results are consistent with a recent report that dismisses the elongation-delaying effects of SD-like sequences (2). The in vivo results also are in line with the recently published discussion on this subject (13,30,42,49). Taken together, the iNP method appears to be suitable for detecting translational pausing that is robust enough to lead to the accumulation of distinct polypeptidyl-tRNA species (see Discussion for further comparisons of the iNP and the ribosome-profiling results).…”
Section: Inp Detection Of Pausing That Is Mediated By Previously Propsupporting
confidence: 86%
See 1 more Smart Citation
“…The in vitro results are consistent with a recent report that dismisses the elongation-delaying effects of SD-like sequences (2). The in vivo results also are in line with the recently published discussion on this subject (13,30,42,49). Taken together, the iNP method appears to be suitable for detecting translational pausing that is robust enough to lead to the accumulation of distinct polypeptidyl-tRNA species (see Discussion for further comparisons of the iNP and the ribosome-profiling results).…”
Section: Inp Detection Of Pausing That Is Mediated By Previously Propsupporting
confidence: 86%
“…They are integral parts of regulatory nascent polypeptides that monitor cellular physiology by undergoing regulated translational arrest (10,11). Arrest sequences interact with the ribosomal components at the peptidyl transferase center and/or the exit tunnel to interfere with the peptidyl transfer, translocation, or termination functions of the ribosome (12)(13)(14)(15). They are diverse in length and primary sequences; translation arrest is either inducible with a specific small molecule or is intrinsic but is subject to release by a physical pulling force that is applied to the nascent chain (10,16,17).…”
mentioning
confidence: 99%
“…Furthermore, unlike the elongation arrest in SecM, which requires prolyl-tRNA in the A-site, that of VemP does not require a specific A-site amino acid; the P-site VemP 1-156 -tRNA did not even receive efficient termination reaction when the A-site was programmed by a stop codon. Although the ribosome-tethered VemP 1-156 -tRNA likely interferes with the ribosomal peptidyl transferase activity, the mode of its action is also different from that used by MifM, which induces multisite stalling of the B. subtilis ribosome, but not the E. coli ribosome (24,44). We showed that VemP can stall the ribosomes from V. alginolyticus and E. coli, both being gram-negative, equally well.…”
Section: Discussionmentioning
confidence: 76%
“…Sequence alignments (Fig. 2D), as well as comparison with the structures of the B. subtilis 70S ribosome (29) and S. aureus 50S subunit (30) (Fig. S2) Interaction of EVN and AVI with H89 and H91 of the 23S rRNA.…”
Section: Resultsmentioning
confidence: 99%